1986
DOI: 10.1073/pnas.83.24.9403
|View full text |Cite
|
Sign up to set email alerts
|

The human prothymosin alpha gene is polymorphic and induced upon growth stimulation: evidence using a cloned cDNA.

Abstract: Clones for human prothymosin a have been identified in cDNA libraries from staphylococcal enterotoxin A-stimulated normal human lymphocytes and from simian virus 40-transformed fibroblasts. The 1198-base-pair fibroblast clone has been sequenced. The encoded protein is highly acidic (54 residues out of 111) and shares >90% sequence homology with rat prothymosin a. The peptide "hormone" thymosin al appears at positions 2-29 of the prothymosin a amino acid sequence. There is no N-terminal signal peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
0
40

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(145 citation statements)
references
References 35 publications
6
99
0
40
Order By: Relevance
“…Together with our recent finding that overexpression of a-prothymosin is restricted to well-defined tumour nodules and to vaso-invading cancer cells in rat HCC rather than to non-tumour regeneration nodules (Wu et al, 1997b), these data suggest that the enhanced transcription of a-prothymosin is associated with HCC. As other evidence supports the view that a-prothymosin is involved in cellular proliferation (Eschenfeldt and Berger, 1986;Eilers et al, 1991;Sburlati et al, 1991), we considered the possibility that overexpression of a-prothymosin might be due to benign liver regeneration nodules that may coexist in HCC tissue. To test this possibility, we have studied mRNA levels of a-prothymosin in patients with only cirrhosis and in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with our recent finding that overexpression of a-prothymosin is restricted to well-defined tumour nodules and to vaso-invading cancer cells in rat HCC rather than to non-tumour regeneration nodules (Wu et al, 1997b), these data suggest that the enhanced transcription of a-prothymosin is associated with HCC. As other evidence supports the view that a-prothymosin is involved in cellular proliferation (Eschenfeldt and Berger, 1986;Eilers et al, 1991;Sburlati et al, 1991), we considered the possibility that overexpression of a-prothymosin might be due to benign liver regeneration nodules that may coexist in HCC tissue. To test this possibility, we have studied mRNA levels of a-prothymosin in patients with only cirrhosis and in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, an accumulating body of evidence suggests that a-prothymosin is associated with cell proliferation, although the precise mechanism remains to be elucidated. For instance, a-prothymosin mRNA was found in proliferating lymphoma and transformed 3T3 fibroblast cells but not in resting cells (Eschenfeldt and Berger, 1986), and antisense RNA or synthetic antisense DNA oligomers of a-prothymosin were able to inhibit cell division in myeloma cells (Sburlati et al, 1991). More interestingly, a-prothymosin gene transcription was shown to be directly regulated by activated c-myc in vitro (Eilers et al, 1991) via an E-box element localized in the first intron of the a-prothymosin gene (Gaubatz et al, 1994).…”
mentioning
confidence: 99%
“…More than 10,000 copies per cell of ProTα are found in kidney, liver, spleen, normal lymphocytes (predominantly T cells), human T-cell leukemia virus-infected T cells and myeloma cells (B-cell lineage) (Eschenfeldt and Berger, 1986). Several studies have demonstrated ProTα's function in immune regulatory activity and potentiation of the immune system (Cordero et al, 1991;Oates et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The protein is neither a precursor for processed polypeptides nor specifically associated with the thymus nor a member of a family with ␤ or ␥ homologues (1)(2)(3). Instead, it is probably the most acidic naturally occurring polypeptide in the eukaryotic world, with 54 carboxyl groups in 109 amino acids, resulting in an isoelectric point at or below pH 3.5 (1,2,4). The mRNA for prothymosin ␣ is distributed ubiquitously among mammalian nucleated cells and tissues (1).…”
mentioning
confidence: 99%